Keputusan Pembelian Ditinjau dari Promosi Menggunakan Media Sosial dan Word of Mouth Marketing - Mahardhika, Mustafidah; Arintowati, Dyan (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2021)
The purpose of this research is to determine the effect of promotion using social media and word of mouth marketing on purchasing decisions for beauty clinic services. This research is belonging to quantitative research with data collection techniques using interviews, documentation, and questionnaires. For data analysis using multiple linear regression analysis. The results showed that at this time, promotions using social media and word of mouth marketing influence purchasing decisions still, either partially or simultaneously. From these results, social media is still effectively used as a tool on promoting products. Word of mouth marketing also has an effective influence in affecting purchasing decisions. Where consumers still trust the recommendations of their close environment on products buying decision. Kata Kunci: social media, word of mouth marketing, buying decision